The main stages of the development of psychological thought in Lithuania (A historical review) - Gučas , A. (Psichologija, 1969)
The article presents a brief review of psychological thought in Lithuania from its origin till the present time. Particular attention is paid to the activities of psychologists in the Soviet period.